Evaluation of the expression of β-catenin and cyclin D1 markers depending on the clinical and morphological characteristics and proliferative activity of colorectal carcinomas - Kharkhalis , I.K.; Shponka , I.S.; Poslavska , O.V. (Морфологія / Morphologia / Morfologìâ, 2022)
Background. Colorectal cancer (CRC) is the third most common malignancy in the world and the fourth most common cause of death from all cancers. The progression of neoplasia in the large intestine depends on a sequence of genetic errors that eventually lead to the appearance of malignant tumors. The earliest known mutation in this progression is the inactivation of the polyposis coli adenomatous tumor suppressor gene. It is important to identify molecular prognostic markers for prognosis, which will help in choosing a therapeutic course of strategy and further improving the survival of patients with CRC. Much attention has been paid to the involvement of cyclin D1 in tumor development and progression. The aim of the study was to evaluate the prognostic significance of the expression of β-catenin and cyclin D1 markers depending on the clinical and morphological characteristics and proliferative activity of colorectal carcinomas. Methods. In the work, the clinical and anatomical material of CRC of 37 patients (15 women and 22 men) who were treated in the 2nd surgical department of the ME “Dnipropetrovsk Regional Clinical Hospital named after I.I. Mechnikova”, Dnipro, Ukraine, in the period from 2019 to 2021. The age of the patients ranged from 27 to 82 years, the average age was 61.43±14.90 years. Primary monoclonal antibodies to Ki-67 (sp6, 1:250), β-catenin (Beta Catenin – 1, clone EP35, RTU), cyclin D1 (clone EP12, RTU) and the UltraVision Quanto imaging system, (LabVision) were used for immunohistochemical research. The photographed fields of view were processed in the Fiji platform with the calculation of the percentages of Ki-67 and cyclin D1 positive intranuclear reactions with the ImmunoRatio plugin. Results. The distribution of variants of typical (membrane) and aberrant (cytoplasmic or cytoplasmic-nuclear) expression of the β-catenin marker demonstrated a significant difference in subgroups of colorectal carcinomas G2 / G3 according to the degree of differentiation (p<0.05), in subgroups with / without metastases (p<0.05) and in subgroups of carcinomas with different proliferative activity (p<0.05). Aberrant (nuclear-cytoplasmic, nuclear dot-like and cytoplasmic with empty nuclei) expression of cyclin D1 in colorectal carcinomas was found much less often (8 out of 37; 21.62%) compared to the β-catenin marker, where atypical reactions accounted for more than half of all cases (24 out of 37; 64.86%). A statistically significant difference in the distribution of aberrant expressions of cyclin D1 was shown in subgroups with different localization (right-sided / left-sided) (p<0.05) and in subgroups with different proliferative activity according to Ki-67 (p<0.05). The highest percentage of high expression of cyclin D1 was demonstrated by right-sided colorectal carcinomas (p<0.05), carcinomas with a moderate degree of G2 differentiation (p<0.05), the subgroup without metastases (p<0.05) and cases of carcinomas with Ki-67 expression >25% (p<0.05).